Olimpismo : the Olympic movement in the making of Latin America and the Caribbean - Sotomayor, Antonio; Torres, César R. (Sport, culture & society (University of Arkansas Press), 2020)
"This book explores the variegated ways in which Latin American and Caribbean societies have been made through their participation in the Olympic Movement since its beginning late in the nineteenth century. The study of the Olympic Movement, in its different manifestations, not just following its European origins, but also considering the agency, struggles, and contributions of Latin American and Caribbean societies to this phenomenon offers a more balanced perspective of the Olympic Movement's history and this region's role in it, while at the same time illuminating the role that the Olympic Movement played in the making of this region. Thus, the book provides potent vistas of the varied ways in which the Olympic Movement has played a significant role in broader social, political, and cultural processes in these societies, and occasionally beyond them. Similarly, it allows to observe and evaluate Latin American and Caribbean influences on the Olympic Movement, as well as the actors and actresses, rationales, and forces at play"--